Edible Bird’s Nest, an Asian Health Food Supplement, Possesses Moisturizing Effect by Regulating Expression of Filaggrin in Skin Keratinocyte - Lai, Queenie Wing Sze; Guo, Maggie Sui Sui; Wu, Kevin Qiyun; Liao, Zhitao; Guan, Dongshi; Dong, Tina Tingxia; Tong, Penger; Tsim, Karl Wah Keung (Frontiers in Pharmacology, 2021)
Edible bird’s nest (EBN) is consumed as a Chinese delicacy for hundreds of years; the functions of which have been proposed to prevent lung disease, strengthen immune response, and restore skin youthfulness. To support the skin function of EBN, the water extract and the further enzymatic digest of EBN having enriched digested peptides were tested in cultured keratinocyte, HaCaT cell line. The effects of EBN extract and digest in inducing proteins crucial for skin moisturizing were determined in both in vitro and ex vivo skin models. In cultured keratinocytes, the expressions of S100-fused type proteins contributing to skin barrier function in the stratum corneum, e.g. filaggrin and filaggrin-2, were determined in both mRNA and protein levels, which were markedly induced in treating of EBN extract or digest. The EBN-induced gene transcriptions of filaggrin and filaggrin-2 were mediated by activation of various transcription factors, e.g. GATA3, PPARα, PPARβ and PPARγ: these transcriptional factors were markedly activated by the digested products of EBN, as compared to the extract, in cultured keratinocytes. By using atomic force microscopy (AFM), the EBN-treated keratinocyte was shown to have more liquid-like morphology, as compared to a control cell. The EBN digest showed better induction on these moisturizing effects as compared to the extract. These lines of evidence therefore suggested the water moisturizing effect of EBN in skin function.